Distance Learning Strategies At SD Muhammadiyah 2 Sidoarjo During the Covid Pandemic-19 - Dwi Febianti; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to find out or describe how distance learning strategies are carried out by Muhammadiyah Elementary School during this pandemic. In this scientific paper, it explains how the strategy carried out by SD Muhammadiyah 2 Sidoarjo was when the pandemic was still at its height, learning in schools used online and if the pandemic had decreased, the school planned to conduct offline learning at school but also must always obey health regulations. . However, in reality, SD Muhammadiyah 2 Sidoarjo still uses the online system, even though there is an appeal from the central government and also the Ministry of Education and Culture to carry out face-to-face learning, but there are one thing or another that causes many parents and guardians of students who do not agree if learning is done face-to-face. Ideas to support the success of distance learning strategies carried out by educators in online learning or on platforms such as Google Classroom, Zoom and Meet, namely, delivery of materials, learning media and teaching materials. This scientific article uses descriptive qualitative method which is a type of qualitative research. Its purpose is to reveal events or facts, phenomena, circumstances and variables that occur when conducting research directly by writing down what actually happened. For data collection techniques using observation and interview techniques. The results of this research at SD Muhammadiyah 2 Sidoarjo show the strategies used in dealing with distance learning, namely, what media are used at SD Muhammadiyah 2 Sidoarjo to deal with distance learning that makes students feel bored. The conclusion that can be drawn is, a distance learning strategy that aims at an online learning process that is directed and can run well.